THE INFLUENCE OF BINGO GAME ON SEVENTH - GRADE STUDENTS’ VOCABULARY MASTERY AT SURYA MANDALA JUNIOR HIGH SCHOOL - Yowa, Mersiana Tanggu; Beeh, Norci; Snae, Alfred (English Education Study Program - Artha Wacana Christian University, 2023)
The title of this research is the influence of bingo games on seventh-grade students' vocabulary mastery at Surya Mandala Junior High School. The research problem: Does bingo games influence seventh-grade students' vocabulary mastery? This research aimed to determine whether the Bingo game's use improves students' vocabulary at Surya Mandala Junior High School. This research method was a pre-experimental design with treatment held in three meetings, 2x40 minutes in each meeting. The writer took 15 students from the VII class as a sample in this research. The research design of this research was one group pre-test and post-test design. The population of this research was Seventh Grade Students of Surya Mandala Junior High School, and the sample was one class. In collecting the data, the writers used tests. The writers used the test instrument in the form of multiple choice and essay tests. For analyzing the data, the writer used Pre-test. The data analysis found that the result of the Pre-Test was 26.67 % of 4 students and post-test 1 was 60% of 9; after applying the bingo game, the last post-test retreatment and playing the game was 100% of 15 students. This result is consulted to the score of the value significant generated Sig. Therefore, H0 is rejected, and Ha is accepted. There is a significant influence of using bingo games on students' vocabulary mastery.